Pengajuan Tagihan Kreditor Terhadap Debitor Setelah Lewat Waktu Pencocokan Piutang - Andani, Devi; Murjiyanto, R.; Sudiyana, Sudiyana (DIVERSI : Jurnal Hukum, 2025)
After the Commercial Court determines the bankruptcy decision, no later than 14 days the supervisory judge must set a deadline for submitting claims by creditors to the curator for debt matching. However, if creditors only find out about the bankruptcy decision after debt matching, what efforts can creditors make? This research aims to find out the Application for Filing Creditors' Claims After the Time for Determining the Distribution of Bankruptcy Assets so that we can find out how the application for submitting creditor's bills after the time for determining the distribution of bankruptcy assets has passed so that it can provide certainty in repayment of debtors' debts as a form of protection for creditors as well as studying and knowing the consequences. request for submission of a creditor's claim after the time for determining the distribution of bankruptcy assets for either the debtor or the creditor itself has expired. This research is a type of qualitative research that follows the typology of normative legal research. Research data was collected through literature and document studies including primary, secondary, and tertiary data. The data that has been collected will be identified and arranged systematically to be relevant to related theories, written descriptively, and analyzed qualitatively. The results of the study show that submission of debt claims by overdue creditors can be done by referring to Article 133 paragraph (1) of the Bankruptcy Law and PKPU, if there are receivables that are then entered after the end of the grace period determined by the supervisory judge and have not been reconciled, then The supervising judge can match the receivables. Then through Decision Number 497 K/Pdt.Sus-Pailit/2014, the Supreme Court in its cassation rejected the creditor's claim because his position as a concurrent creditor meant that debt payments for bankruptcy cases would only be paid if there was money left to pay them.